2017
DOI: 10.3389/fmicb.2017.00370
|View full text |Cite
|
Sign up to set email alerts
|

Rhoptry protein 5 (ROP5) Is a Key Virulence Factor in Neospora caninum

Abstract: Neospora caninum, of the Apicomplexa phylum, is a common cause of abortions in cattle and nervous system dysfunction in dogs. Rhoptry proteins of Apicomplexa play an important role in virulence. The objectives of this study were to study functions of NcROP5 in N. caninum by deleting the NcROP5 gene from the wild Nc-1 strain. We selected NcROP5 in ToxoDB and successfully constructed an NcROP5 gene-deleted vector, pTCR-NcROP5-CD KO. Then we screened the NcROP5 knockout strains (ΔNcROP5) at the gene, protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…So we must understand these phenotypes in future study. A recent study showed that the loss of NcROP5 by N. caninum led to a reduction in mouse mortality and reduced NcGRA7 transcription in the parasite (12). According to ToxoDB, sequences that share high identity with TgROP5 (TgROP5A, TgROP5B, and TgROP5C) have been detected the genome of the N. caninum Liverpool strain: NcLIV_060730, NcLIV_060740, and NcLIV_060741, respectively (12,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So we must understand these phenotypes in future study. A recent study showed that the loss of NcROP5 by N. caninum led to a reduction in mouse mortality and reduced NcGRA7 transcription in the parasite (12). According to ToxoDB, sequences that share high identity with TgROP5 (TgROP5A, TgROP5B, and TgROP5C) have been detected the genome of the N. caninum Liverpool strain: NcLIV_060730, NcLIV_060740, and NcLIV_060741, respectively (12,29).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the loss of NcROP5 by N. caninum led to a reduction in mouse mortality and reduced NcGRA7 transcription in the parasite (12). According to ToxoDB, sequences that share high identity with TgROP5 (TgROP5A, TgROP5B, and TgROP5C) have been detected the genome of the N. caninum Liverpool strain: NcLIV_060730, NcLIV_060740, and NcLIV_060741, respectively (12,29). On the contrary, RNA sequencing in this study showed no significant differences in the expression levels of Neospora ROP5 in Nc1 and the NcGRA7-deficient and NcGRA7-complemented lines (see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After identification at the genomic level, protein level, transcription level, and protein distribution, we verified that the NcGRA6 strain was successfully generated and could be used for further NcGRA6 gene function research. In N. caninum, the NcSRS2 protein was used as a surface protein in GRA17 and ROP5 gene knockout strains (31,34). During identification of the NcGRA6 strain at the protein level, we first labeled the specific putative surface protein NcSRS22A in N. caninum using its monoclonal antibody (identified and prepared in our laboratory) to explore the location of GRA6 protein.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the influence of NcGRA6 in N. caninum virulence, we conducted experiments both in vitro and in vivo. Plaque, invasion, egress, and replication assays are common technologies for the applied in in vitro parasite virulence research (31,34). In our study, we performed these assays to compare virulence changes between the N. caninum NcGRA6 strain and Nc-1 strain.…”
Section: Discussionmentioning
confidence: 99%